Using Virtual Reality to Study Subjective Time in Crowded Versus Uncrowded Environments. Issue 5 (October 2019) - Shimokawa, Kazuma; Sugimori, Eriko
Human density in different locations influences time estimation. In this article, we report three experiments investigating whether research in virtual reality (VR) environments would replicate this earlier finding. In our first experiment, 35 participants wore head-mounted VR displays and watched two videos showing a cityscape and a countryside. While watching each video, participants were asked to provide their perceptions of 30 seconds of time passage. Perceived time in the cityscape condition was longer than in the countryside condition. In our second experiment, 43 participants wore head-mounted VR displays and watched two videos showing a crowded and uncrowded Ikebukuro station. While watching these videos, participants were asked to provide their perceptions of 60 seconds of time passage. Perceived time in the crowded condition was longer relative to the uncrowded condition. In our third experiment, 21 participants wore head-mounted displays and watched two videos showing a crowded and uncrowded nature park. While watching the videos, participants were asked to provide their perceptions of 60 seconds of time passage. These repeated findings in VR environments of longer time perception in crowded versus uncrowded conditions were similar to data reported by who examined how location and human density affected subjective time in the real world. We discussed the implications of the VR tool in subjective time research and how people perceive and use VR environments in daily life.